2021
DOI: 10.3389/fmicb.2021.695445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Energy Levels on Rumen Fermentation, Gastrointestinal Tract Histology, and Bacterial Community Diversity in Fattening Male Hu Lambs

Abstract: This study investigated rumen fermentation and histological and microbial diversity in male Hu lamb fed diets with different metabolizable energy (ME) levels (MEA, 9.17 MJ/kg, MEB, 10.00 MJ/kg, and MEC, 10.82 MJ/kg). Thirty-six male Hu lambs were randomly allotted to three treatments, and the feeding trial lasted for 67 days. Rumen fermentation results suggest that the iso-valerate had a significant effect on dietary energy level. The papillary height (PH) of rumen was the highest in the MEB group, the crypt d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
3
10
1
Order By: Relevance
“…The PICRUSt prediction results showed that amino acid metabolism, carbohydrate metabolism, replication and repair, membrane transport, translation, and energy metabolism were the dominant gene families at KEGG level 2, all of which are essential for survival, growth, and reproduction of gastrointestinal microbes (44). These results were similar to our previous studies in sheep (11)(12)(13)(14)(15). Among these gene families, unexpectedly, the genes associated with metabolism of cofactors and vitamins, cellular processes and signaling, metabolism, biosynthesis of other secondary metabolites, infectious diseases, signaling molecules and interaction, nervous system, and digestive system were significantly higher in the PSR silage diet than in the mixed and corn silage diets, while lipid metabolism was dramatically lower in the PSR silage diet than in the corn silage diet.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The PICRUSt prediction results showed that amino acid metabolism, carbohydrate metabolism, replication and repair, membrane transport, translation, and energy metabolism were the dominant gene families at KEGG level 2, all of which are essential for survival, growth, and reproduction of gastrointestinal microbes (44). These results were similar to our previous studies in sheep (11)(12)(13)(14)(15). Among these gene families, unexpectedly, the genes associated with metabolism of cofactors and vitamins, cellular processes and signaling, metabolism, biosynthesis of other secondary metabolites, infectious diseases, signaling molecules and interaction, nervous system, and digestive system were significantly higher in the PSR silage diet than in the mixed and corn silage diets, while lipid metabolism was dramatically lower in the PSR silage diet than in the corn silage diet.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, the concentration of GLU in the mixed group was significantly lower than in the PSR silage and corn silage treatments, while the higher ADG was observed in the mixed group. These results were inconsistent with previous studies, and this might be related to species and feed composition (11)(12)(13)(14)(15). The concentration of BUN is perceived as an effective indicator to measure the metabolism of protein and amino acid, low BUN level indicates high nitrogen metabolism capacity (21).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Prevention and of treatment obesity are thus very important for modern societies. Intriguingly, mounting evidence suggests that gut microbiota is related to obesity and its associated metabolic disorders. Furthermore, transplanting the gut microbiota from obese donors to germ-free recipients by fecal microbiota transplantation (FMT) leads to obesity phenotypes in recipients, thereby verifying the cause–effect relationship between gut microbiota and obesity. , Gut microbiota dysbiosis impairs the intestinal redox state and integrity, increases endotoxin levels in the circulatory system, and induces metabolic inflammation, eventually resulting in the development of obesity. , Recently, certain inflammatory/pathogenic gut bacteria, including Desulfovibrio and Parasutterella, have been found to worsen obesity, whereas certain genera or species of beneficial gut bacteria, including Lactobacillus, Bifidobacterium, Akkermansia muciniphila, and Bacillus coagulans, could alleviate obesity. Therefore, the modulation of gut microbiota dysbiosis has been presented for the prevention and treatment of obesity. …”
Section: Introductionmentioning
confidence: 99%